2017
DOI: 10.1016/j.humpath.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of autopsy case–based learning into PhD graduate education: a novel approach to bridging the “bench-to-bedside” gap

Abstract: Given the current rapid expansion of biological knowledge and the challenges of translating that knowledge into clinical practice, finding effective methods of teaching graduate students clinical medicine concepts has become even more critical. The utility of autopsy in medical student and resident education has been well established. Multiple studies have reported it to be a helpful means of teaching anatomy, pathophysiology, clinical problem-solving skills, and medical diagnostic techniques. Although various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These findings are in line with several types of relative earlier researches, demonstrating that the use of real patients reinforcing the clinical application of basic science knowledge, and performing an active motivational context. CBL is a powerful learning strategy for medical students at undergraduate level education as well as for professional development (Mehmet et al 2014;Raurell-Torreda et al 2015;Yoo and Park 2015;Brooks et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with several types of relative earlier researches, demonstrating that the use of real patients reinforcing the clinical application of basic science knowledge, and performing an active motivational context. CBL is a powerful learning strategy for medical students at undergraduate level education as well as for professional development (Mehmet et al 2014;Raurell-Torreda et al 2015;Yoo and Park 2015;Brooks et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore necessary to increase the use of autopsies as a learning tool in undergraduate education. 13,15,35 This will change the attitudes and interests of the medical profession and nursing staff in clinical autopsies and could eventually increase the number of autopsies requested. Education will improve the ability of medical and nursing staff to communicate more effectively with relatives regarding the purpose of autopsies and the value of the information that is currently often inaccurate and incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…12 Autopsies have traditionally been used in undergraduate medical education; however, in recent decades, they have stopped being an important teaching tool, although several studies have confirmed their value. 8,[13][14][15][16][17] Burton and Underwood 18 state in their review in Lancet 2007 that autopsies are underused in clinical practice and highlight the importance of the fact that many doctors are not familiar with autopsy routines and underestimate their value.…”
Section: Introductionmentioning
confidence: 99%